2020
DOI: 10.1021/acsami.9b21077
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Ir-CoOx@mesoporous SiO2 Nanoreactors for Selective Hydrogenation of Substituted Nitroaromatics

Abstract: Nanosized Ir catalysts suffer from serious side reactions and poor stability during hydrogenation of substituted nitroaromatics to produce aromatic amines. In this work, core−shell nanostructures with sub-4 nm Ir-CoO x hybrid cores and mesoporous SiO 2 shells were designed and prepared to overcome these problems. The Ir-CoO x hybrid cores were converted from IrCo alloy nanoparticles (NPs) inside SiO 2 through in situ calcination and reduction pretreatments. The SiO 2 mesoporous shells in Ir-CoO x @SiO 2 nanore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
0
26
0
Order By: Relevance
“…The limited number of sampled Pd particles in such a wide size distribution detected by STEM as shown in Figure b may not be representative of the overall distribution . The residual chloride in the 3CEDI­(NaOH)-200k-600 (Cl: 0.49%) sample caused a H 2 chemisorption shortfall, leading to a smaller measured Pd dispersion, which was also reported by Regalbuto et al The results from XRD, TEM, STEM, and H 2 chemisorption demonstrated that the electrostatic interaction between [Pd­(NH 3 ) 4 ] 2+ and the deprotonated surface hydroxyls on SiO 2 remained strong enough to avoid severe sintering of Pd nanoparticles during reduction at 600 °C in the SEA and CEDI preparation, agreeing well with previous reports. In comparison to the CEDI preparation, a higher amount of alkali (or alkali/SiO 2 ratio) was used in the SEA preparation (Table S1), resulting in efficient deprotonation of the surface hydroxyl of SiO 2 and complete adsorption of [Pd­(NH 3 ) 4 ] 2+ on the SiO 2 support. Thus, the Pd/SiO 2 -SEA samples (Pd dispersion > 50%) showed a higher palladium dispersion than the Pd/SiO 2 -CEDI samples (Pd dispersion = 32%–45%).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The limited number of sampled Pd particles in such a wide size distribution detected by STEM as shown in Figure b may not be representative of the overall distribution . The residual chloride in the 3CEDI­(NaOH)-200k-600 (Cl: 0.49%) sample caused a H 2 chemisorption shortfall, leading to a smaller measured Pd dispersion, which was also reported by Regalbuto et al The results from XRD, TEM, STEM, and H 2 chemisorption demonstrated that the electrostatic interaction between [Pd­(NH 3 ) 4 ] 2+ and the deprotonated surface hydroxyls on SiO 2 remained strong enough to avoid severe sintering of Pd nanoparticles during reduction at 600 °C in the SEA and CEDI preparation, agreeing well with previous reports. In comparison to the CEDI preparation, a higher amount of alkali (or alkali/SiO 2 ratio) was used in the SEA preparation (Table S1), resulting in efficient deprotonation of the surface hydroxyl of SiO 2 and complete adsorption of [Pd­(NH 3 ) 4 ] 2+ on the SiO 2 support. Thus, the Pd/SiO 2 -SEA samples (Pd dispersion > 50%) showed a higher palladium dispersion than the Pd/SiO 2 -CEDI samples (Pd dispersion = 32%–45%).…”
Section: Resultsmentioning
confidence: 70%
“…Both the WI and DI methods suffer from poor metal precursor–support interaction during metal deposition, especially when using “inert” supporting materials (SiO 2 , carbon, etc. ), resulting in severe sintering and a wide size distribution of metal particles during the thermal treatment. Thus, several innovative methods have been developed to prepare noble metal nanoparticles (NPs) with a narrow size distribution and high dispersion on support. Among them, strong electrostatic adsorption (SEA) and charge-enhanced dry impregnation (CEDI) methods have been proven to be simple and cost-effective to prepare supported noble and base metal catalysts with high dispersion and tight size distribution of metal particles. The SEA and CEDI methods involve a simple variation in the WI and DI methods, respectively, using an initially strongly acidified or basified impregnating solution according to the support’s point of zero charge (PZC) to enhance the electrostatic interaction between the metal ion/cation precursor and protonated/deprotonated surface hydroxyls on support. This strong interaction stabilizes the metal precursors during drying and prevents the metal particles from severe aggregation during thermal treatment, as opposed to WI and DI. , …”
Section: Introductionmentioning
confidence: 99%
“…Two characteristic bands at 2077 and 2044 cm –1 are clearly observed for Ir/Al 2 O 3 . The former is assigned to gemdicarbonyl adsorbed CO on the Ir sites while the latter is indexed to the linear adsorbed CO on metallic Ir. , The Ir–CoO x /Al 2 O 3 exhibits a band at 2070 cm –1 for gemdicarbonyl adsorbed on Ir and a shoulder band at 2044 cm –1 for linear CO adsorbed on Ir. We speculate that the significantly weaker band for linear CO adsorbed on Ir–CoO x /Al 2 O 3 is possibly due to the less exposure of Ir surfaces by partial coverage of CoO x .…”
Section: Resultsmentioning
confidence: 99%
“…Since the XPS signals of Ir–MO x /Al 2 O 3 with real Ir loadings of ∼1.6 wt % are very weak, the unsupported Ir–MO x NPs prepared by calcination and following the reduction of IrM NPs were used for the analyses. Considering that the binding energies of Co 3p and Ir 4f are partially overlapped, we selected Co 2p and Ir 4d to evaluate their chemical states. According to the literature, , the binding energies at 296.2–296.5 and 311.4–311.7 eV in Figure a are assigned to 4d 5/2 and 4d 3/2 of the Ir 0+ species, respectively, while those at 299.0–300.0 and 314.2–315.2 eV are indexed to the Ir δ+ species existing in Ir and Ir–CoO x NPs due to the surface oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation